A big picture perspective of the decolonization of Public Administration debate in Africa: Looking back and looking forward - Nzewi, O. I.; Maramura, T. C. (Stellenbosch University, 2021)
Trailblazing discussions on "decolonisation" have continuously been building up since Kwame Nkrumah's Pan-Africanist ideological constructs, but not much has been undertaken regarding the rebuilding of the fibre of the Public Administration curriculum. As a result, literature has been embedded in a lot of nuances in decoding the concept of decolonization. Amongst these narratives is the tendency to distinguish the decolonization of the curriculum as a mere African exhilaration which is disguised as a counter-construct to colonization. In light of the adverse effects of colonization on the African curriculum, critical reflections that shoot from a broad review of decolonization approaches in Public Administration are unveiled in this article. The aim is to encourage institutions of higher learning to apply a decolonizing approach that appreciates the pedagogical value of indigenous knowledge relating to Public Administration as a locus and as a focus. The article also covers an exposition revealing how decolonization of the Public Administration curriculum is neither an "anti-West" fad nor a dissuasion to learn from the West and the globalized village. It does this by taking full cognizance of the past without disintegrating the already polarized social fabric. It is against this background that it becomes imperative that South Africa begins to rediscover, and regenerate its local values by enabling the practicalities of decolonizing the curriculum through extending examples in practice. If university repositories and research hubs are going to be reliably contributing to the transformation of the African continent and the global village at length, then it is obvious that the teaching material and how it is delivered will have to certainly change somehow. The article then explores alternatives and sustainable solutions that can be proffered in accelerating the relevance of the alternative indigenous knowledge systems on the Public Administration curriculum.